2007
DOI: 10.4103/0378-6323.37055
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis: Clinico-mycologic study of 130 patients from Himachal Pradesh, India

Abstract: Onychomycosis is not uncommon in this part of the country and has similar clinico-mycologic profiles in the different cases detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 0 publications
3
20
1
2
Order By: Relevance
“…However, nail specimen cultures in the present study showed highly positive results for the presences of fungal organisms which are in accordance with Raghavendra et al The isolated fungal results in our study are compatible with many other studies reported that dermatophytes, mainly Trichophyton rubrum "T. rubrum", as the most common fungal organisms involved in onychomycosis followed by yeasts, mainly candida albicans ''C. albicans'', in many countries as Great Britain, Egypt and India [5,13,[20][21][22][23][24]. Biofilm has become the focus of the era and is considered to be one of the important causes of chronic recalcitrant infections globally.…”
Section: Discussionsupporting
confidence: 82%
“…However, nail specimen cultures in the present study showed highly positive results for the presences of fungal organisms which are in accordance with Raghavendra et al The isolated fungal results in our study are compatible with many other studies reported that dermatophytes, mainly Trichophyton rubrum "T. rubrum", as the most common fungal organisms involved in onychomycosis followed by yeasts, mainly candida albicans ''C. albicans'', in many countries as Great Britain, Egypt and India [5,13,[20][21][22][23][24]. Biofilm has become the focus of the era and is considered to be one of the important causes of chronic recalcitrant infections globally.…”
Section: Discussionsupporting
confidence: 82%
“…[28] The increased prevalence of toenail infection in males could be the result of more traumas in the nails and the more common use of occlusive footwear. Finger nails were also more frequently affected than toenails in many other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic paronychia is an inflammatory disorder of the proximal nail fold, reactive to irritants and allergens2,3,4. When the cuticle separates from the nail plate, the region between the proximal nail fold and nail plate is vulnerable to infection by bacterial and fungal pathogens3.…”
mentioning
confidence: 99%
“…When the cuticle separates from the nail plate, the region between the proximal nail fold and nail plate is vulnerable to infection by bacterial and fungal pathogens3. Colonization with C. albicans or bacteria may occur in the lesion2,4. Paronychia is associated with 84.2% of candidal onychomycosis; the initial paronychia leads to nail discoloration, and then, dystrophy ensues4.…”
mentioning
confidence: 99%
See 1 more Smart Citation